Clinical Study to Evaluate the Efficacy of Lekhaniya Mahakashaya in the Management of Medoroga w.s.r. to Dyslipidemia - Gupta, Poonam; Mahajan, Nitin (International Research Journal of Ayurveda & Yoga, 2021)
Dyslipidemia is a life style disorder related to lipo-protein metabolism. It is a silent disorder with a high rate of complications, morbidity like cardio-vascular diseases diabetes, hyper-tension, atherosclerosis, etc. and mortality. It is manifested as i) rise in plasma levels of total cholesterol, triglycerides or both ii) decrease in HDL level and iii) increase in LDL and VLDL levels. It can be correlated to Medoroga. In present clinical study, 30 patients suffering from Medoroga were selected from O.P.D and I.P.D. of Jammu Institute of Ayurveda and Research, Jammu. Written and informed consent of patients was taken before inclusion in the trial. It was a Prospective Open Clinical Trial. So, only one group with 30 patients was administered Lekhaniya Mahakashaya in Ghana form filled in capsule of 500 mg. in the dose of 3 gm/day in three divided doses (2 capsules TDS) with Ushanodaka before meals for 45 days. All the patients were statistically analyzed before and after the treatment.